Bridging the miscibility gap towards higher thermoelectric performance of PbS. (November 2021) - Cheng, Rui; Wang, Dongyang; Bai, Hui; Wu, Jinsong; Liu, Wei; Zhao, Li-Dong; Tang, Xinfeng; Tan, Gangjian
Abstract: Forming solid solutions between two isostructural compounds is an important strategy of regulating thermal transport in solids and boosting thermoelectric performance of narrow gap semiconductors. However, its full potential is not reached in a large variety of systems because of the known miscibility gap. A typical example includes PbS-PbTe where a limited solubility is demonstrated for one in another. Here in this study we show that the miscibility gap between PbS and PbTe is well bridged by introducing 30 mol% PbSe. This considerably extends the solubility limit of PbTe from only ∼4 mol% in PbS to at least 16 mol% in PbS0.7 Se0.3, thus remarkably reducing the lattice thermal conductivity from a solid solution point of view. More importantly, it is found that carrier mobility of PbS is negligibly affected by this heavy alloying process, which is against conventional knowledge that higher concentration of defects leads to stronger carrier scattering. Our electron localization functions (ELF) mapping calculation results suggest an increased overlap of the adjacent electron clouds and decreased periodic potential fluctuations when the miscibility gap between PbS and PbTe gets bridged by PbSe. Therefore, the strengthened chemical bond covalency of PbS upon PbSe/PbTe alloying is responsible for the well reserved carrier mobilities. The simultaneous optimization of electron and phonon transport enabled by miscibility gap engineering (also applicable to many other technologically important thermoelectric materials) greatly boosts the thermoelectric performance of n-type Ga-doped PbS, leading to an excellent peak ZT of ∼1.1 at ∼723 K together with a record high average ZT value of 0.73 (300-723 K) in the samples of Pb0.99 Ga0.01 S0.7-x Se0.3 Tex ( x ≥ 0.12). Graphical abstract: By introducing 30 mol% PbSe, the miscibility gap between PbS and PbTe is well bridged, leading to much reduced lattice thermal conductivity. More importantly, the carrier mobility of PbS is negligibly affected by this heavy alloying process because of strengthened chemical bond covalency. Altogether, an excellent peak ZT of ∼1.1 at ∼723 K together with a record high average ZT value of 0.73 (300-723 K) was achieved. Image, graphical abstract